How do you simplify \frac { 40x ^ { 2} - 27x - 7} { 5x + 1}40x227x75x+1?

2 Answers
Jan 21, 2018

(40x^2-27x-7)/(5x+1)=8x-740x227x75x+1=8x7

Explanation:

(40x^2-27x-7)/(5x+1)40x227x75x+1

= (40x^2-35x+8x-7)/(5x+1)40x235x+8x75x+1

= (5x(8x-7)+1(8x-7))/(5x+1)5x(8x7)+1(8x7)5x+1

= ((5x+1)(8x-7))/(5x+1)(5x+1)(8x7)5x+1

= 8x-78x7

Jan 21, 2018

:. x = 7/8

Explanation:

Use Trinomial Factoring on the Numerator:

= (8x-7)(5x+1) // (5x+1)

Divide Out Like Terms or Simply Cross Them Out:

= (8x-7)(cancel(5x+1)) // (cancel(5x+1))

Isolate for x:

= (8x-7)

:. x = 7/8